Interaction effect between blood selenium levels and stroke history on all-cause mortality: a retrospective cohort study of NHANES - Li, Yanli; Liu, Lanqun; Yang, Zufu; Xu, Jimin (Frontiers in Neurology, 2024)
Aim The study aimed to investigate the interaction effect between blood selenium levels and stroke history on all-cause mortality. Methods In this retrospective cohort study, participant data were obtained from the National Health and Nutrition Examination Survey (NHANES) 2011–2018. The covariates were screened via the backward selection method in weighted univariate and multivariate Cox regression models. Weighted univariate and multivariate Cox regression models were conducted to investigate the association of blood selenium and stroke history with all-cause mortality. The results were expressed as hazard ratios (HRs) and 95% confidence intervals (CIs). The synergy index (SI) was used to assess the assistive interaction. The association was further explored in different gender groups. Results Totally, 8,989 participants were included, of whom 861 (9.57%) died. Participants with blood selenium ≥192.96 ug/L were associated with lower odds of all-cause mortality (HR = 0.70, 95% CI: 0.58–0.84), whereas those with a stroke history were associated with a higher risk of all-cause mortality (HR = 1.57, 95% CI: 1.15–2.16). Compared to participants with blood selenium ≥192.96 ug/L and non-stroke history, participants with both blood selenium < 192.96 ug/L and stroke history had a higher all–cause mortality risk (HR = 2.31, 95% CI: 1.62–3.29; SI = 0.713, 95% CI: 0.533–0.952). All participants with blood selenium < 192.96 ug/L and stroke history were related to higher all–cause mortality risk (HR = 1.61, 95% CI: 1.21–2.13). In males, the interaction effect of blood selenium and stroke history on all–cause mortality (HR = 2.27, 95% CI: 1.50–3.46; SI = 0.651, 95% CI: 0.430–0.986) increased twice. Conclusion Blood selenium and stroke history have an interaction effect on all-cause mortality. Increasing selenium-rich food or supplement intake, especially for individuals with a stroke history, may improve poor prognosis.